2020
DOI: 10.3310/hsdr08310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased distance to urgent and emergency care facilities resulting from health services reconfiguration: a systematic review

Abstract: Background Service reconfigurations sometimes increase travel time and/or distance for patients to reach their nearest hospital or other urgent and emergency care facility. Many communities value their local services and perceive that proposed changes could worsen outcomes for patients. Objectives To identify, appraise and synthesise existing research evidence regarding the outcomes and impacts of service reconfigurations tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Our study's results show a consistent reduction in in-hospital mortality across municipality groups, suggesting that if the reconfiguration has affected mortality, this has occurred uniformly across municipalities, irrespective of emergency hospital status. Like other studies, 8,23,24 our results suggest that AMI contacts in municipalities with increased distance to emergency departments have not experienced the improved mortality documented for other contacts-suggesting that residents living the farthest away from an acute hospital do not achieve the improvement effects that closer residents benefit from. Patient trajectories are very complex, and our study does not point to whether a problem might be present for AMI contacts.…”
Section: Interpretation Within the Context Of The Wider Literaturesupporting
confidence: 66%
See 2 more Smart Citations
“…Our study's results show a consistent reduction in in-hospital mortality across municipality groups, suggesting that if the reconfiguration has affected mortality, this has occurred uniformly across municipalities, irrespective of emergency hospital status. Like other studies, 8,23,24 our results suggest that AMI contacts in municipalities with increased distance to emergency departments have not experienced the improved mortality documented for other contacts-suggesting that residents living the farthest away from an acute hospital do not achieve the improvement effects that closer residents benefit from. Patient trajectories are very complex, and our study does not point to whether a problem might be present for AMI contacts.…”
Section: Interpretation Within the Context Of The Wider Literaturesupporting
confidence: 66%
“…12 In terms of the effect of increased distance travelled to emergency departments seen in this study, previous studies have shown that increased distance to emergency departments is not associated with increased mortality in the general population requiring emergency care. 23,24 The only exceptions were acute myocardial infarcts and trauma, for which the risk of mortality increased for both groups in the first few years after reorganization. 23,24 Fløjstrup et al have documented a downward trend in the in-hospital mortality in Denmark, which is consistent with this study's results.…”
Section: Interpretation Within the Context Of The Wider Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Citation searching offers a potential response to such search challenges. The exemplar systematic review showcased in this study was undertaken over 7 months, between January and July 2019 (Chambers, Cantrell, et al, 2020).…”
Section: The Context For Our Investigationmentioning
confidence: 99%